2007
DOI: 10.1007/s00402-007-0326-7
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of the distal biceps brachii tendon: conservative treatment versus anatomic reinsertion—clinical and radiological evaluation after 2 years

Abstract: Our findings confirm the view that anatomic repair of distal biceps tendon rupture provides consistently good results and early anatomic reconstruction can restore strength and endurance for the elbow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
77
0
19

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 10 publications
2
77
0
19
Order By: Relevance
“…1,2 With distal biceps injury, forearm supination and, to a lesser extent, elbow flexion strength and endurance can be compromised by over 40%, [3][4][5][6] and significant pain can result due to persistent traction on the lacertus fibrosus or residual tendon. Consequently, direct primary repair of distal biceps rupture remains the hallmark for treatment, particularly with more acute injuries.…”
mentioning
confidence: 99%
“…1,2 With distal biceps injury, forearm supination and, to a lesser extent, elbow flexion strength and endurance can be compromised by over 40%, [3][4][5][6] and significant pain can result due to persistent traction on the lacertus fibrosus or residual tendon. Consequently, direct primary repair of distal biceps rupture remains the hallmark for treatment, particularly with more acute injuries.…”
mentioning
confidence: 99%
“…4 In addition to this clinical study, numerous papers have shown superior strength and endurance in patients who have had tendon reconstruction. [5][6][7][8][9] Single-incision surgical reconstructions using an isolated anterior approach are possible owing to the development of a variety of suture anchor devices that facilitate the attachment of tendon to bone. These anchors allow the surgeon to approach and reattach the tendon using a single anterior approach.…”
mentioning
confidence: 99%
“…This is due in large part to the fact that multiple studies have shown superior functional outcomes after surgical treatment such as increased supination and flexion strength and decreased fatigability. [3][4][5][6] Although operative treatment has shown improved outcomes, the optimal technique for distal biceps tendon repair remains controversial. Anatomic repair can be performed through a 1-incision approach or a 2-incision approach.…”
mentioning
confidence: 99%